The Influence Of Remote Work On Innovation Work Behavior With Work Life Behavior And Technostress As Moderating Variables - Annisa Grandisia Forza; Sidiq Permono Nugroho (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Currently, the advent of presence technology has significantly transformed human lifestyle patterns. Technological advancements have brought about changes and innovations in work systems, leading to the creation of new tools that simplify user experiences in social media. The aim of of this research is to examine and analyze the influence of remote work on innovative work behavior, with work-life balance and technostress as intervening variables. This research method uses research quantitative using a sampling technique, namely purposive sampling. Meanwhile, samples studied as many as 209 respondents which consists of employees and freelancers from technology-based companies in Surakarta. Who participated in filling out 36 online survey questions via Google form. The methodology in the current research combined the use of the Smart-PLS analysis tool version 3.0 software application with the structural equation model (SEM). The results of this research: Innovative work behavior has a substantial and beneficial effect on the remote work variable. Work-life balance suffers greatly from the remote work variable. Technostress has a substantial impact on the remote work variable. The work-life balance variable substantially and favorably influences innovative work behavior. Innovation work behavior has a profoundly beneficial effect on the technostress variable. Through work-life balance, mediation confirms that remote work has an enormous and beneficial effect on innovative work behavior, as supported by the statistical t-value. Through technostress, mediation exhibits that remote work has a favorable and noteworthy impact on innovative work behavior.